What storytelling tells us about fantasy: parent-child stories about emotionally-charged real and fantastic events. Issue 14 (26th October 2021) - Carrick, Nathalie; Richmond, Rebecca
ABSTRACT: This study examined parent-child storytelling for insights into children's fantastical thinking. We targeted differences in storytelling based on story genre (fictional-reality and fictional-fantasy) emotion, and storyteller, and how dyads treated fantasy within the stories. 49 3- to 5-year-olds and their parents told stories based on images that depicted either human or anthropomorphic animal protagonists who expressed happiness, fear, or sadness. Results reveal that variations in storytelling varied mainly by emotion and storyteller and less by story genre, and that fantastic information was treated somewhat conservatively. Findings point to storytelling as a context in which focus is placed on reality more than fantasy.